A Systematic Multiple Studies Review of Low-Income, First-Generation, and Underrepresented, STEM-Degree Support Programs: Emerging Evidence-Based Models and Recommendations - Jill Pearson; Lisa A. Giacumo; Arvin Farid; Mojtaba Sadegh (MDPI AG, 2022)
The dramatic lack of diversity within science, technology, engineering, and mathematics (STEM) higher-education graduates is a serious issue facing the future of the STEM workforce. Colleges and universities are attempting to fix this disparity through targeted intervention programs aimed at increasing the persistence and retention of low-income, first-generation, and underrepresented (UR) students in STEM. A comprehensive synthesis of adopted strategies and analysis of their effectiveness is lacking. We conducted a systematic multiple-studies review, considering 31 empirical articles published between 2005 and 2020 that shared the outcomes of intentional intervention programs in place across the United States. We uncovered essential characteristics of successful programs and highlighted the top 10 critical program components to consider. These can be used to guide the development and execution of future programs' support systems and interventions. This is a relatively new area of research, with most programs just in the earliest stages of implementation. It is essential to continue to follow the data on the outcomes of these programs, particularly their longitudinal impacts on the diversification of the STEM workforce, to be able to implement effective evidence-based practices.